The Keloid Area and Severity Index (KASI): an objective tool for the evaluation of keloids. (1st November 2022) - Limmer, Emily E.; Kerby, Eva; Lies, Shelby; Limmer, Byron; Limmer, Rachel; Teske, Noelle; Savory, Stephanie; Reisch, Joan S.; Glass, Donald A.
Abstract: To aid in the standardization of evaluating patients with multiple keloids, a Keloid Area and Severity Index (KASI) was developed using patient feedback, previous literature, and clinical expertise. The system was validated using intrarater and interrater reliability assessments. Here, we present a verified, reliable method of assessing keloid area and severity in clinical and research settings.